2018
DOI: 10.1007/s10815-018-1147-z
|View full text |Cite
|
Sign up to set email alerts
|

Embryonal mitochondrial DNA: relationship to embryo quality and transfer outcomes

Abstract: Although the mtDNA content shows some association to the morphologic grade of an embryo, this association does not persist in an analysis of only euploid embryos. Mitochondrial DNA content also does not appear to be associated with implantation or ongoing pregnancy. Day 5 blastocysts have significantly higher mtDNA content compared to day 6 blastocysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 38 publications
11
49
1
Order By: Relevance
“…However, in this study we did not observe any correlation between maternal age (24-46 years) at the time of oocyte retrieval and mtDNA levels in trophectodermal cells of blastocyst. Similar to our findings, other studies also failed to report any correlation between maternal age with mtDNA levels in the blastocysts (de Los Santos et al, 2018; Diez-Juan et al, 2015; Klimczak et al, 2018; Victor et al, 2017). Together the results indicate, maternal age does not contribute to alterations in mtDNA levels in the blastocysts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in this study we did not observe any correlation between maternal age (24-46 years) at the time of oocyte retrieval and mtDNA levels in trophectodermal cells of blastocyst. Similar to our findings, other studies also failed to report any correlation between maternal age with mtDNA levels in the blastocysts (de Los Santos et al, 2018; Diez-Juan et al, 2015; Klimczak et al, 2018; Victor et al, 2017). Together the results indicate, maternal age does not contribute to alterations in mtDNA levels in the blastocysts.…”
Section: Discussionsupporting
confidence: 92%
“…On the basis of this hypothesis, various studies have analyzed the levels of mtDNA and its association of the developmental competence. Studies have reported high levels of mtDNA in poor quality embryos (de Los Santos et al, 2018; Diez-Juan et al, 2015; Klimczak et al, 2018; Murakoshi et al, 2013). Interestingly, in our study, we did not find any correlation between morphological grading of blastocysts and mtDNA levels in the trophectodermal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies reported that an increased mtDNA copy number is related to aneuploidy and a decreased embryo implantation potential [23,26]. However, there have been other studies contradicting these findings [66,67]. All of these studies used different methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to speculation that IVF treatments could be optimized by screening for mtDNA content when embryos are being selected for implantation, rejecting all those with higher mitochondrial densities [135]. However, follow-up studies have failed to replicate these results, finding no association between the mtDNA content of early human blastocysts and either the age of the mother or the likelihood of the blastocyst becoming implanted [137,138]. At present, it seems likely that the discrepancies between studies are due to differences in the way in which samples are either collected, stored, or analysed [138,139], and the true relationship between maternal age and mitochondrial content of the early embryo remains to be resolved.…”
Section: (C) Mitochondrial Ageing In the Germlinementioning
confidence: 99%